ANALISIS PEMANFAATAN TESLA COIL DALAM MENGHASILKAN TRANSMISI DAYA TANPA KABEL - Al Farizi Ade Karlin Kusuma; Siti Awaliyah Saripah; Amelia Rahma (Cross-border, 2023)
Tesla coil or tesla coil is a high frequency and high voltage transformer developed by Nikola Tesla. Tesla coil is used to produce wireless power transmission by inserting metal rods into the ground. Then, the earth will become a conductor that supplies power throughout the world. The purpose of this paper is to analyze the use of the Tesla coil in producing wireless power transmission. The method used in this paper is descriptive analysis of several journals and research results in utilizing the Tesla coil to produce wireless power transmission. Some of the conclusions obtained are that the more coils it will increase the transmission of electric power without wires. In addition, the number of turns affects the amount of flux produced by the tesla coil. The use of tesla coils has proven to be effective and efficient in transmitting power without wires and has the potential for future technological advances.